UPAYA PENINGKATAN READING COMPREHENSION MATERI DESCIPTIVE TEXT MELALUI MODEL PEMBELAJARAN TIPE COOPERATIVE SCRIPT BAGI SISWA SMA NEGERI 9 KOTA JAMBI - RONALD FRANSISKUS GULTOM (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2022)
This study aims to improve reading comprehension (Reading Comprehension) of Desciptive Text Materials through a Cooperative Script Type Learning Model for Students of SMA Negeri 9 Jambi City in the 2019/2020 Academic Year. The research method used is classroom action research (CAR). Researchers used data collection methods in the form of qualitative and quantitative. Qualitative data is taken by looking at the results of observations and quantitative results. Quantitative data is taken from the scores of students' test results which were analyzed with descriptive statistics. The target of the research was class X MIPA 1 SMA Negeri 9 Jambi City, totaling 36 students. Researchers used two cycles. Each cycle consists of planning, action, observation, and reflection. Researchers found several findings. The research data showed that the students' reading comprehension increased from pre-test to post-test. The average score of students is 62.78, while the first post-test shows an average value of 73.06, and the second post-test average value is 79.03. The increase in the percentage of students' scores that exceed the KKM on the reading test is 61.12% to 94%. Decrease in the percentage of students who do not exceed the KKM from 38.88% to 2%. That is, the Cooperative Script Type Learning Model can be used to improve students' Reading Comprehension. ABSTRAKPenelitian ini bertujuan untuk meningkatkan pemahaman membaca (Reading Comprehension) Materi Desciptive Text Melalui Model PembelajaranTipe Cooperatif Script Bagi Siswa SMA Negeri 9 Kota Jambi Tahun Pelajaran 2019/2020. Metode penelitian yang digunakan adalah penelitian tindakan kelas (PTK). Peneliti menggunakan metode pengumpulan data berupa kualitatif dan kuantitatif. Data kualitatif diambil dengan melihat hasil dari observasi dan hasil kuantitaif. Data quantitative diambil dari nilai hasil test siswa yang dianalisa dengan deskriptif statistik. Sasaran penelitian adalah kelas X MIPA 1 SMA Negeri 9 Kota Jambi yang berjumlah 36 siswa. Peneliti menggunakan dua siklus. Setiap siklus terdiri dari perencanaan, tindakan, observais, dan refleksi. Peneliti menemukan beberapa penemuan. Data hasil penelitian menunjukan bahwa kemampuan membaca (Reading Comprehension) siswa meningkat daro pre-test ke post-test. Nilai rata-rata siswa menujukan 62.78, sementara post-test pertama menunjukan nilai rerata 73.06, dan nilai rerata post-test kedua addalah 79.03. Peningkatan presentase nilai siswa yang melampaui KKM pada test membaca yaitu 61.12% menjadi 94%. Penurunan presentase siswa yang tidak melampaui KKM dari 38.88% menjadi 2 %. Artinya, Model PembelajaranTipe Cooperatif Script bisa digunakan untuk meningkatkan kemampuan membaca (Reading Comprehension) siswa.